DAMPAK SEMINAR ENTREPENEUR REMAJA TERHADAP PEMBANGUNAN UMKM DI DESA CISARUA - Fauzia, Amelia; Hikmah Jasun, Nur; Fadilah, Nova; Sabrina, Ina (LPPM Politeknik Pajajaran ICB Bandung, 2022)
Cisarua Village has a lot of potential for Micro, Small and Medium Enterprises (MSMEs) originating from agriculture and plantations. This study aims to analyze and identify the problems faced and develop strategies for the development of Micro, Small and Medium Enterprises (MSMEs) in Cisarua Village, Cikole District, as one of the leading sectors in helping to improve the economy of the people of Cisarua Village, Cikole District, Pandeglang. This research method uses qualitative methods through the process of observation, interviews, and documentation presented in the form of data, then analysis uses a SWOT matrix analysis to find out strengths, weaknesses, opportunities and threats. Cisarua Village, implementation time 40 days. The results of this study indicate that there are problems in every Micro, Small and Medium Enterprises (MSMEs) actor in Cisarua Village such as: lack of awareness from youth to continue existing businesses, as well as open new business opportunities, capital, marketing, human resources, facilities and infrastructure, introduction to technology, social and economics, so that the development of MSMEs in Cisarua Village, Cikole District, has not been carried out properly. While the right strategy is carried out in the development of MSMEs in Cisarua Village, Cikole District, this is a strategy that utilizes existing strengths to increase their competitive advantage.